Psiquiatria e cuidados primários. Uma experiência de ligação. - A M Botelho; M P Delgado (Acta Médica Portuguesa, 1997)
Psychiatric problems are common in general medical practice. This paper reviews information supporting the need to integrate psychiatry and general medical practice. The two year liaison between the psychiatric ward of Santa Maria Hospital and Sete Rios Medical Centre is described. A model of longitudinal case supervision analogous to that used in psychiatric residency training to provide knowledge and skills in mental health can respond to the needs of general practitioners.